O romance como antídoto em Jean-Jacques Rousseau - SILVA, Priscila de Oliveira (2017)
Jean-Jacques Rousseau, despite living in the 18th century, it is different from their contemporaries by not look with optimism that the Enlightenment, considered the centuries of Lights, brought to society. As for the intellectual community the society came to an apex of moral progress and scientific developments with the Enlightenment Having as basic principle the reason, continuing the movement started by the Renaissance, that is, to use the rational knowledge against ignorance, superstition and belief. Rousseau says in his work entitled The Discourse on the sciences and the arts that science, the arts and letters alienate man from his natural state, and stifle their freedom. However, soon the philosopher is accused of contradiction, because even cursing the letters, launches the novel Julia or the New Heloise under the pretext of writing it with the end moral of protecting the readers of a society corrupted. The critique of the Rousseau was also for another reason: the novel was seen as a narrative frivolous and immoral because it is a tale of fiction, and as contrary to the rational order and the canons Aristotelian. In this way, it was necessary to analyze the emergence and the rise of the narrative romance within a cultural landscape and epistemological in contrast to classical aesthetics. Next, we investigated the entry and the originality of Rousseau in romanticism and the fracture with the classical aesthetic. Subsequently, we trace the trajectory of humanity corrupted by Rousseau in the discourse on the origin and the inequality between men, as well as the trajectory of the history of language until the language in the essay on the origin of languages, these two concepts of philosophy rousseauniana. And, finally, we tried to investigate the alleged paradox of Rousseau, like him, a critic of the letters, also be a writer of romance, and with the moral justification to retain people.